2017
DOI: 10.1073/pnas.1612311114
|View full text |Cite
|
Sign up to set email alerts
|

Field-scale experiments reveal persistent yield gaps in low-input and organic cropping systems

Abstract: Knowledge of production-system performance is largely based on observations at the experimental plot scale. Although yield gaps between plot-scale and field-scale research are widely acknowledged, their extent and persistence have not been experimentally examined in a systematic manner. At a site in southwest Michigan, we conducted a 6-y experiment to test the accuracy with which plot-scale crop-yield results can inform field-scale conclusions. We compared conventional versus alternative, that is, reduced-inpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 37 publications
3
73
0
Order By: Relevance
“…While the above ground vegetative biomass on a dry weight basis was 4.5% higher in CONV grown plants, the below ground vegetative biomass on a dry weight was 6% greater in organically (ORG) grown plants ( Supplementary Table 1). The observed reduction in yield and biomass under ORG fertilizer is as expected since the use of organic fertilizer has been implicated in the reduction of yield by 5-34% [4].…”
Section: Agronomic and Phytonutrient Analysissupporting
confidence: 73%
“…While the above ground vegetative biomass on a dry weight basis was 4.5% higher in CONV grown plants, the below ground vegetative biomass on a dry weight was 6% greater in organically (ORG) grown plants ( Supplementary Table 1). The observed reduction in yield and biomass under ORG fertilizer is as expected since the use of organic fertilizer has been implicated in the reduction of yield by 5-34% [4].…”
Section: Agronomic and Phytonutrient Analysissupporting
confidence: 73%
“…Year effects on yield were high as well in our study, following the same pattern as that observed for total amount of BNF: 2008 > 2007 > 2006. In the "Scale up" experiment that involves 27 fields at the Kellogg Biological Station (where the LFL trial is located) a strong seasonal weather effect was also observed, where soybean yields varied from ~1 to 3 MG ha -1 depending on the year (Kravchenko et al, 2017).…”
Section: Soybean Yieldmentioning
confidence: 99%
“…What are the main controlling factors that facilitate the combined ISFM component (dis)adoption? These are among the most common questions that researchers and extension agents in southern Africa try to have prior answers to as they advance the technologies tested on small plots to the wider community (Maat, ; Kravchenko et al, ). To date, several technologies have been developed through scientific experiments and rolled out to farms through onā€farm demonstrations.…”
Section: Introductionmentioning
confidence: 99%